Identification of two polymorphic microsatellite repeats on a bovine TNFA-containing BAC clone - Wambugu, J.; Kanguha, E.; Hanotte, Olivier H.; Davis, S.; Taylor, J.; Skow, L.; Brunner, R.; Schwerin, M.; Teale, A.J.; Iraqi, F.A. (2001)
Two bovine bacterial artificial chromosome clones were screened by PCR to amplify the tumour necrosis factor alpha (TNFA) gene. DNA extraction and Southern blotting and probing with a (GT)10 oligonucleotide were performed, followed by cloning into the pUC19 vector. A 0.9 kb fragment containing sequences homologous with the probe was sequenced and a (GT)9 microsatellite was identified. Further DNA sequencing for the subclones yielded a (TA)10(TTA)5 microsatellite. Primers were designed to amplify these 2 microsatellites in 4 cattle breeds. The PCR product length was polymorphic as shown by denaturing polyacrylamide gel electrophoresis. The microsatellites were designated as ILFI-TNF-I and II for (GT)9 and (TA)10(TTA)5, respectively.